O processo de gramaticalização do uso de tanto que (e variantes) em corpus dos séculos XIII, XIII~XIV, XV, XVI, XVII e XIX - Bellay, Regiane (2011)
The theme of functionalist theory of grammaticalization of elements of clauses is approached in this paper in order to analyze the grammaticalization of so that. The comprehension of so that behavior is the importance that justify the existence of this research. As specific objectives it has the searches of: moment that so that begins to occur only as consecutive function; what can justify this process of grammaticalization; what can point the existence of correlation between consecutive and temporal corpora. The corpus analyzed diachronically through the method type (temporal conjuctive locution; quantifier I, II and III) and token (284 occurrences) is composed of: Dos costumes de Santarém (XIII); Vidas de Santos de um Manuscrito Alcobacense (XIII ~ XIV centuries) includes Vida de Tarsis, Vida de uma Monja, Vida de Eufrosina, Visão de Túndalo, Vida de Santa Pelágia, Morte de São Jerônimo and Visão de Santa Maria Egipcíaca; corpus from XV century (História dos reis de Portugal em Crônica Geral de Espanha and Orto do esposo); Crônica dos reis de Bisnaga (XVI); Corpus from XVII century (Sermão de Santo Antônio aos peixes and Compêndio da relação que veio da Índia no ano de 1691); corpus from XIX century (Descobrimento das Filipinas pelo navegador português Fernão de Magalhães and Memória dos feitos macaenses contra os piratas da China e da entrada violenta dos ingleses na cidade de Macao). We have the extinction of so that as time in the nineteenth century in the corpus studied, what points to a different level of grammaticalization to so that as consecution that continues to occur until the present day and it is analyzed traditionally in consecutive subordinate clauses, but there is a classification focused on the correlation, by the differences between subordinated and correlative behavior that are differentiated by so that behavior as time and by so that behavior as consecutive.